Dynamic of Аntarctic tourism at Faraday/Vernadsky station (1968–2008) - Fedchuk, A.P. (Український антарктичний журнал, 2008)
Few previous site-specific studies have given attention to the development and management issues of Antarctic tourism at operating scientific stations that support non-governmental activities to some degree. This article presents findings from a study that examined the change in visitor patterns at Ukrainian Vernadsky Station (formerly British Faraday Station), one of the most visited tourist destinations in the Antarctic Peninsula area. Data detailing the trends of tourist activities at Faraday/Vernadsky Station have been collected and processed from 195 to 2008. Since 1996 there have been significant changes in governance and policy resulting in the increasing tourist numbers. This study uses a comparative approach to examine regulation patterns at different scientific stations in Antarctica and indicates policies for better visitor management at Vernadsky Station.